Answer:
C. y +3 = x +3
Explanation:
We need to find in below option x has direct variation with y.
We solve for each;
A.
![2y = 3x-7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/41879dqnf3c0odijcq9mhqma0krnbhr9ql.png)
From above equation we can state that 2 times y is equal to 7 less than 3 times of x.
Hence it doesn't represent direct variation.
B.
![y-4 = x+6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kva6kpwr1u0lgztiork5gcuzf7qw4j7888.png)
Solving above expression we get;
![y-4 = x+6\\y = x+6+4\\y=x+10](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8n9j7u6t5san01im9q6q0quwqlf7de3zh7.png)
From above equation we can state that y is equal to 10 more than x.
Hence it doesn't represent direct variation.
C.
![y+3 = x+3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fltoxtt0tfmsx2t9i0ry49g2e6t93iubki.png)
Solving above expression we get;
![y+3 = x+3\\y = x+3-3\\y=x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9qufj5zxe1z0ynxwlvofqgs8fezhazk43h.png)
From above equation we can state that y is equal to x.
Hence it represent direct variation.
D.
![4y+1 = 4x-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/t6cbviidoykahu2shq01ipp8g45f5dsk0i.png)
Solving above expression we get;
![4y+1 = 4x-1\\4y = 4x-1-1\\4y=4x-2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ylq6h7uasuvgg3qeflmtme1zu9gmylsx1k.png)
From above equation we can state that 4 times y is equal to 2 less than 4 times of x.
Hence it doesn't represent direct variation.
Hence the Answer which represent direct variation of x and y is,
C.
![y+3 = x+3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fltoxtt0tfmsx2t9i0ry49g2e6t93iubki.png)